Gait initiation in progressive supranuclear palsy: brain metabolic correlates - Chiara Palmisano; Massimiliano Todisco; Giorgio Marotta; Jens Volkmann; Claudio Pacchetti; Carlo A. Frigo; Gianni Pezzoli; Ioannis U. Isaias (NeuroImage: Clinical, 2020)
The initiation of gait is a highly challenging task for the balance control system, and can be used to investigate the neural control of upright posture maintenance during whole-body movement. Gait initiation is a centrally-mediated motion achieved in a principled, controlled manner, including predictive mechanisms (anticipatory postural adjustments, APA) that destabilize the antigravitary postural set of body segments for the execution of functionally-optimized stepping. Progressive supranuclear palsy (PSP) is a neurodegenerative disease characterized by early impairment of balance and frequent falls. The neural correlates of postural imbalance and falls in PSP are largely unknown. We biomechanically assessed the APA at gait initiation (imbalance, unloading, and stepping phases) of 26 patients with PSP and 14 age-matched healthy controls. Fourteen of 26 enrolled patients were able to perform valid gait initiation trials. The influence of anthropometric and base-of-support measurements on the biomechanical outcome variables was assessed and removed. Biomechanical data were correlated with clinical findings and, in 11 patients, with brain metabolic abnormalities measured using positron emission tomography and 2-deoxy-2-[18F]fluoro-D-glucose. Patients with PSP showed impaired modulation of the center of pressure displacement for a proper setting of the center of mass momentum and subsequent efficient stepping. Biomechanical measurements correlated with “Limb motor” and “Gait and midline” subscores of the Progressive Supranuclear Palsy Rating Scale. Decreased regional glucose uptake in the caudate nucleus correlated with impaired APA programming. Hypometabolism of the caudate nucleus, supplementary motor area, cingulate cortex, thalamus, and midbrain was associated with specific biomechanical resultants of APA. Our findings show that postural instability at gait initiation in patients with PSP correlates with deficient APA production, and is associated with multiple and distinctive dysfunctioning of different areas of the supraspinal locomotor network. Objective biomechanical measures can help to understand fall-related pathophysiological mechanisms and to better monitor disease progression and new interventions.